Comparative analysis of acids and temperatures in gelatin extraction from the skin of yellowfin tuna (Thunnus albacares) - Vicky Prajaputra; Sri Agustina; Nadia Isnaini; Agillia Nabila; Hikma Kasih Margolang; Sahra Apriani; Siti Maqfirah (Depik, 2024)
Gelatin, a valuable biopolymer, is commonly derived from animal by-products such as fish skin, providing a sustainable alternative to traditional bovine and porcine sources. The extraction process is influenced by factors like acid type and temperature, which impact both yield and quality. This study aimed to compare the effects of citric acid and acetic acid, at two temperatures (50C and 60C), on the gelatin extracted from yellowfin tuna (Thunnus albacares) skin. The extracted gelatin was evaluated for yield, proximate composition, functional groups using FTIR, and surface morphology through SEM. Results indicated that acetic acid produced a significantly higher yield than citric acid at both temperatures, with the highest yield (10.10%) at 50C and the lowest (2.46%) from citric acid at 60C. Gelatin extracted with acetic acid also had higher protein content and lower moisture and ash levels. FTIR analysis confirmed the presence of characteristic gelatin functional groups, including Amide I, II, and III. SEM images showed a denser and more uniform structure in acetic acid-extracted gelatin, while gelatin extracted with citric acid had a more porous and irregular surface. SDS-PAGE analysis revealed stronger protein bands for gelatin extracted with acetic acid, indicating higher protein content and a more efficient extraction process. Both acid-extracted gelatins showed -chains and -chains, characteristic of denatured collagen. In conclusion, acetic acid proved to be more effective than citric acid in producing higher yield and superior quality gelatin from yellowfin tuna skin. Further studies should assess the gel strength and amino acid composition of the extracted gelatin.Keywords:environmental chemistrybelow waterbiopolymergelatinmarine chemistrywaste valorizationyellowfin tuna